Mitotic and DNA Damage Response Proteins: Maintaining the Genome Stability and Working for the Common Good - Luna-Maldonado, Fernando; Andonegui-Elguera, Marco A.; Díaz-Chávez, José; Herrera, Luis A. (Frontiers in Cell and Developmental Biology, 2021)
Cellular function is highly dependent on genomic stability, which is mainly ensured by two cellular mechanisms: the DNA damage response (DDR) and the Spindle Assembly Checkpoint (SAC). The former provides the repair of damaged DNA, and the latter ensures correct chromosome segregation. This review focuses on recently emerging data indicating that the SAC and the DDR proteins function together throughout the cell cycle, suggesting crosstalk between both checkpoints to maintain genome stability.